PERAN MEDIA SOSIAL INSTAGRAM @BPBDPROVINSISUMUT DAN @INFOBMKGSUMUT DALAM PENYEBARAN INFORMASI BENCANA BANJIR DI SUMATERA UTARA - Khairani, Mutiara Malshara; Purba, Ikhwan Azizi; Ginting, Rahmanita (Linimasa : Jurnal Ilmu Komunikasi, 2026)
Flood disasters in North Sumatra Province show an increasing trend, both in terms of the frequency of occurrences and the magnitude of their impacts, thereby necessitating adaptive and responsive crisis communication strategies that address community needs. In this context, Instagram has become an important medium for disseminating disaster-related information to the public. This study aims to analyze the role of Instagram in the dissemination of flood disaster information in North Sumatra through a case study of the official accounts @bpbdprovinsisumut and @infobmkgsumut, using the perspectives of contemporary communication theory, crisis communication theory, and agenda-setting theory. The research employs a descriptive qualitative approach with content analysis techniques applied to posts and user interactions during the disaster period. The findings indicate a complementary division of roles: the @infobmkgsumut account is more dominant in the pre-disaster phase by delivering early warning information based on meteorological data, while the @bpbdprovinsisumut account focuses on the emergency response and post-disaster phases through evacuation information and the coordination of aid. The use of visual elements such as infographics and field documentation has proven effective in simplifying technical messages so they are easily understood by the public. However, the communication pattern applied remains predominantly one-way and institutional in nature, with limited emphasis on empathy and the narratives of victims’ experiences. In addition, the management of two-way interactions in the comment sections has not been optimally utilized as a channel for reporting residents’ emergency conditions. This study concludes that Instagram has evolved into a dynamic social space in disaster management, yet strengthening human-centered message framing strategies is still necessary.